The Implications in Implementation of the Acquisition of TikTok Shop with Tokopedia based on Regulation of Business Law in Indonesia - Riani, Maulina Desita; Untoro, Untoro (Universitas Islam Sultan Agung, 2024)
On 4 October 2023, TikTok announced that it had closed buying and selling transactions on the TikTok Shop platform. This decision was taken in response to the Minister of Trade Regulation (Permendag) Number 31 of 2023 concerning Business Licensing, Advertising, Guidance, and Supervision of Business Actors in Trading through Electronic Systems which was recently enacted. The legal research method used in this research is normative juridical research which is research carried out or aimed only at written regulations with the nature of descriptive analysis research, which is a method that functions to describe or provide an overview of the object under study. The data source used is secondary data with quantitative data analysis. The results of this research are now TikTok Shop is running as usual by cooperating with Tokopedia, which has a marketplace licence and is still incorporated in the same application on 12 December 2023. The merger of the two companies raises the possibility of a potential monopoly in the E-commerce industry, as these two companies are two big players or companies in this industry that control most of the E-commerce market share in Indonesia, so that it can make players or E- commerce in Indonesia more competitive. So to overcome this, TikTok needs to apply for a business licence as a marketplace that is separate from its social media application to the Ministry of social media application to the Ministry of Trade, so that the position of the two applications stands on its own to prevent unfair business competition in the E-commerce industry and protect MSMEs and personal data leaks.